A STUDY ON THE EFFECT OF ETHANOL EXTRACT OF RADIX RHAPONTICI ON ERYTHROCYTE IMMUNE FUNCTION IN RATS - Yan, Xiang; Zhao, Hong; Guan, Yin; Song, Yanbin; Meng, Jing (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
This paper mainly studied the effect of ethanol extract of Radix Rhapontici on erythrocyte immune function in SD rats with acute blood stasis. The methods used the effect on erythrocyte immune function. After intragastric administration of suspension of ethanol extract of Radix Rhapontici to SD rats for 3 weeks, on the 21st day from intragastric administration, SD rats were made into blood stasis model and bloods were collected to determine the C3b, C3bRR, RFIR, and RFER in erythrocyte immune function. Meanwhile, serum total antioxidant activity (TAA), superoxide dismutase (SOD) activity, and serum malondialdehyde (MDA) level of rats were determined, and experimental results were analysed with analysis of variance and Q test. The results showed that the ethanol extract of Radix Rhapontici had a very good effect on enhancement of erythrocyte immune function in SD rats.